2004
DOI: 10.1021/tx040001v
|View full text |Cite
|
Sign up to set email alerts
|

Human Cytochrome P450 Enzyme Specificity for Bioactivation of Safrole to the Proximate Carcinogen 1‘-Hydroxysafrole

Abstract: In the present study, the cytochrome P450 mediated bioactivation of safrole to its proximate carcinogenic metabolite, 1'-hydroxysafrole, has been investigated for the purpose of identifying the human P450 enzymes involved. The 1'-hydroxylation of safrole was characterized in a variety of in vitro test systems, including Supersomes, expressing individual human P450 enzymes to a high level, and microsomes derived from cell lines expressing individual human P450 enzymes to a lower, average human liver level. Addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 11 publications
0
62
0
Order By: Relevance
“…For safrole, CYP2A6 is the most efficient human enzyme involved in 1 0 -hydroxylation at physiologically relevant concentrations [Jeurissen et al, 2004[Jeurissen et al, , 2007. In a recent study, Jeurissen et al [2007] identified CYP1A2 and CYP2A6 as the most important enzymes in estragole 1 0 -hydroxylation, while CYP1A2 has been identified by this group [2006] as the major enzyme catalyzing the 1 0 -hydroxylation of methyleugenol.…”
Section: Discussionmentioning
confidence: 99%
“…For safrole, CYP2A6 is the most efficient human enzyme involved in 1 0 -hydroxylation at physiologically relevant concentrations [Jeurissen et al, 2004[Jeurissen et al, , 2007. In a recent study, Jeurissen et al [2007] identified CYP1A2 and CYP2A6 as the most important enzymes in estragole 1 0 -hydroxylation, while CYP1A2 has been identified by this group [2006] as the major enzyme catalyzing the 1 0 -hydroxylation of methyleugenol.…”
Section: Discussionmentioning
confidence: 99%
“…The CYP enzymes involved in the bioactivation of safrole to its proximate carcinogen 19-hydroxysafrole in man were identified to be CYP2C9, CYP2A6, CYP2D6, and CYP2E1 [94,95]. Data from Gentest microsomes in which the activities towards enzyme-selective substrates are considered to be in the same order as the mean activities found in human liver microsomes, reveal CYP2A6 to contribute about two times more than the other CYPs that are active in safrole 19-hydroxylation [94].…”
Section: Polymorphisms Of Influencementioning
confidence: 97%
“…Human CYP enzymes involved in the formation of the 1 -hydroxy metabolite of estragole, methyl eugenol and safrole were evaluated (Jeurissen et al, 2004(Jeurissen et al, , 2005(Jeurissen et al, , 2007. Safrole was incubated either with Supersomes (baculovirus-infected insect cell microsomes that express individual human CYP enzymes to a high level) or with microsomes derived from cell lines that express individual human CYP enzymes to a lower, more typical human liver level.…”
Section: Related Biochemistry Studiesmentioning
confidence: 99%
“…Based on research performed since the late 1990s (Gardner et al, 1997a(Gardner et al, , 1997bWakazono et al, 1998;Jeurissen et al, 2004Jeurissen et al, , 2005Jeurissen et al, , 2007Ueng et al, 2004), significant induction of the CYP activation pathway is expected to successively convert alkoxy-substituted allylbenzenes into their 1 -hydroxy metabolites and sulfate conjugates. This is especially prevalent at higher dose levels in rodents.…”
Section: Summary Of Enzyme Induction and Adduct Formation Datamentioning
confidence: 99%